Acute and lagged fitness consequences for a sagebrush obligate in a post mega‐wildfire landscape. Issue 1 (24th December 2021) - Anthony, Christopher R.; Foster, Lee J.; Hagen, Christian A.; Dugger, Katie M.
Abstract: Species responses to disturbance influence their extinction risks. Greater sage‐grouse ( Centrocercus urophasianus ) are bioindicators of sagebrush ecosystem health and the loss of sagebrush ( Artemisia spp.) due to wildfire, can cause long‐term declines in sage‐grouse populations and other sagebrush obligate species. We examined the demographic response of a greater sage‐grouse population following a mega‐wildfire using stochastic age‐structured female‐based matrix models over 6 years (2013–2018). Notably, chick survival (range = 0.18–0.38) and female survival (yearling range: 0.20–0.68; adult range: 0.27–0.75) were low compared to values reported for greater sage‐grouse in other parts of their distribution. Greater sage‐grouse displayed variation in demographic tactics after the fire; however, adult female survival explained most of the variation in λ during each year, which reflected a declining population in 3 of 6 years with more uncertainty observed in 2015 when populations may have been increasing, and 2017 and 2018, when populations may have been declining. The continued annual population decline observed since 2016 suggested there were additional strong environmental impacts that may have been compounded by the fire effects, prolonging recovery of greater sage‐grouse. Our results support others that reported negative effects to greater sage‐grouse demographics from broad‐scale fire and provide a baseline for understanding how this species responds to loss of sagebrush cover based on their life history strategy. Abstract : Chick survival and female survival were low for Greater sage‐grouse a megafire, compared to values reported throughout their range. Greater sage‐grouse exhibited variation in demographic tactics; however, adult female survival explained most of the variation in the finite rate of population change, which reflected a declining population in 3 of 6 years following the fire.